Contemporary Developments and Perspectives in International Health Security - Volume 2 2021
DOI: 10.5772/intechopen.96583
|View full text |Cite
|
Sign up to set email alerts
|

Autistic Spectrum Disorder in the Context of Pandemic by Covid-19: Caring for Children and Caregivers

Abstract: The COVID-19 pandemic has brought important challenges to society and families, with repercussions on child behavior and development with special importance for children with neurodevelopmental disorders that affect and impair the child’s functionality: Autism spectrum disorder. Thus, we set as objective to Identify and analyze the scientific evidence of interventions performed on children with Autism Spectrum Disorder in the context of a Covid-19 pandemic. A search was conducted in the MEDLINE, PubMed, CINHAL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…However, some studies reported contradictory findings where children on the autism spectrum did not display any change in behaviors and psychological outcomes during the lockdown (25), or even displayed marginal improvement in emotional moods and psychopathological dimensions (68) during the pandemic. Individuals on the autism spectrum may be more comfortable at home without the academic and social requirements in school, thus having lower levels of stress during home confinement (17,26,64).…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies reported contradictory findings where children on the autism spectrum did not display any change in behaviors and psychological outcomes during the lockdown (25), or even displayed marginal improvement in emotional moods and psychopathological dimensions (68) during the pandemic. Individuals on the autism spectrum may be more comfortable at home without the academic and social requirements in school, thus having lower levels of stress during home confinement (17,26,64).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the COVID-19 can be even more worrisome in children suffering from autism spectrum disorders. Sudden changes in daily routine have after-effects and can potentiate existing symptoms, increasing the risk of emotional, behavioural and relationship complications [9]. Many autistic people do want friends and to be around other people.…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, these new life circumstances have a deeper impact on the physical and mental health of people of all ages. Several researchers (e.g., Vilelas, 2021;Baweja, 2021;Patel, 2020;Polizi et al, 2020;Schnell & Krampe, 2020;Casagrande et al Kim et al, 2020) refer to the impacts on individuals (adults and children) and their long-term consequences. For example, feelings of powerlessness, health insecurity, economic and job insecurity, stressful experiences, adverse psychological effects, reduced productivity and self-efficacy, frustration, anger, loneliness, constant fear of illness, fear of interacting with other people, sleep disturbances and gastrointestinal problems are just some of the adverse effects that people may experience during the pandemic.…”
Section: The Impact Of Covid-19mentioning
confidence: 99%